(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper is a tribute to the unsung warriors of organisations who brave the daily challenges of chronic illness, cloaked in a conspiracy of silence. The study attempts to present the role of human capital development initiatives in enhancing the psychological well-being of an overlooked section of diversity – Employees with chronic illness. According to the United Nations, even though employment “Provides many opportunities for social participation, from economic independence, to family formation, to a sense of contributing to the national economy” (United Nations 2007, p. 85), worldwide, 80 to 90% of working-age persons with disabilities are unemployed. (United Nations 2010). Chronic Illness literature (Beatty & Joffe, 2006) presents the fact that employees suffering from disability caused by chronic illness are often overlooked in the narratives of positive organisational support and human capital development. One of the main reasons being that disability caused by chronic illness doesn’t follow a predictable path and thus poses a challenge to policy framing. The illnesses range from mild to severe, low interference to high interference, episodic to ongoing, and above all visible to invisible. Chronic diseases are responsible for contributing the largest share to the overall mortality in the developing countries, except for Sub-Saharan Africa (Suhrcke, Nugent, Stuckler, &; Rocco, 2006). Most commonly occurring illnesses include cardiovascular diseases, cancers, diabetes, and chronic respiratory diseases (World Health Organization (WHO), 2018). The other common chronic diseases could be musculoskeletal disorders, multiple sclerosis, epilepsy, migraines and many more.